The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the International Conference Fakultas Tarbiyah Dan Keguruan Universitas Islam Negeri Imam Bonjol Padang - ICFTKU 2020
DOI: 10.32698/icftk417
|View full text |Cite
|
Sign up to set email alerts
|

The role of headmaster in managing the facilities and infrastructure

Abstract: This research is motivated by the progress of facilities and infrastructure at SMP Negeri 9 Payakumbuh. This study used a descriptive qualitative method. Data collection techniques are carried out through observation, interviews and documentation. Data analysis techniques in research are data reduction, data presentation, and conclusions. The results showed: (1) The role of the principal in planning facilities and infrastructure is carried out through coordination with representatives of facilities and infrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Learning using the NHT type cooperative method does have a positive impact on various learning domains. Several previous studies have shown that in general NHT has a positive effect on increasing students' mathematical learning achievement [8]. Learning using the NHT method has also been proven to improve students' critical thinking abilities [9] and problem solving abilities [10].…”
Section: Resultsmentioning
confidence: 99%
“…Learning using the NHT type cooperative method does have a positive impact on various learning domains. Several previous studies have shown that in general NHT has a positive effect on increasing students' mathematical learning achievement [8]. Learning using the NHT method has also been proven to improve students' critical thinking abilities [9] and problem solving abilities [10].…”
Section: Resultsmentioning
confidence: 99%